Endomycobiome associated with females of the planthopper Delphacodes kuscheli (Hemiptera: Delphacidae): A metabarcoding approach - Brentassi, María Eugenia (2020)
A metabarcoding approach was performed aimed at identifying fungi associated with Delphacodes kuscheli (Hemiptera: Delphacidae), the main vector of “Mal de Río Cuarto” disease in Argentina. A total of 91 fungal genera were found, and among them, 24 were previously identified for Delphacidae. The detection of fungi that are frequently associated with the phylloplane or are endophytes, as well as their presence in digestive tracts of other insects, suggest that feeding might be an important mechanism of their horizontal transfer in planthoppers. This study draws the baseline for future research regarding mutualistic associations present in D. kuscheli as well as their physiological role in the life cycle of this important pest that might lead to developing new management strategies to keep insects populations under control.